Pesantren Law; Challenge and Opportunity for Indonesian Islamic Education - Safiudin Safiudin; Ali Muhtarom; Ahmad Qurtubi; Utami Syifa Masfu'ah (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Pondok Pesantren is the oldest educational institution in Indonesia and has a distinctive character of the archipelago that specifically focuses on Islamic religious education (Educational Institution Based Religion). The emergence of colonial-based modern educational institutions presents an interesting dynamic among Pondok Pesantren Which is also called by islamic boarding schools, the Indonesian state with the National Education System continues to strive to build a symbiotic pattern between modern (official state) education and Pesantren, which of course, is expected to be a form of mutualistic relationship, the purpose of this paper is to display the main content of the Pesantren Law, the characteristics of pesantren with a historical perspective and seeks to predict the implications (challenge and opportunity) of the Pesantren Law on the development of Pesantren as an educational institution that is distinctive and has a native Indonesian character. The Method use in this paper is based on library research to find out the literature study of The Challenge and opportunity of Islamic studies based on pesantren law. The result of this paper show that Pesantren law provides a great opportunity for Islamic boarding schools to be able to improve the quality, and quality of the five constituent elements, behind the great opportunities obtained by Islamic boarding schools, there are severe challenges for pesantren after the Pesantren law is implemented.